Digital Payments : Ditinjau Dari Literasi Keuangan Dan Perilaku Konsumtif - Nurma Hayani Syabirin; Suliska, Gita; Marthika, Laula Dwi (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
The development of financial technology has driven a significant increase in the use of digital payments in Indonesia. This phenomenon not only provides ease of transactions but also gives rise to consumptive behavior due to easy access and attractive promotions. This study aims to analyze the influence of financial literacy and consumptive behavior on the use of digital payments in society. The research method used a quantitative approach with a purposive sampling technique and distributed questionnaires to 55 respondents. Data were analyzed using multiple linear regression with the help of SPSS version 25 software. The results showed that financial literacy had no significant effect on the use of digital payments, while consumptive behavior had a positive and significant effect. Simultaneously, both variables significantly influenced the use of digital payments with a contribution of 49.2%. The main discussion reveals that consumptive behavior is the dominant factor driving the use of digital payments, while financial literacy plays a role in controlling digital financial behavior. The implications of this study emphasize the importance of improving financial literacy and education on consumptive behavior so that people can use digital payments wisely, safely, and sustainably in the digital economy era.